The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1097/tp.0b013e318255f890
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Transplantation Alone in ESRD Patients With Hepatitis C Cirrhosis

Abstract: Our study suggests that KTx alone may be safe in patients with compensated HCV, cirrhosis, and ESRD with HPVG less than 10 mm Hg. A simultaneous liver-kidney transplantation may be an unnecessary use of a liver allograft in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 20 publications
3
31
0
Order By: Relevance
“…In their study the negative prognosticators included recipient age and albumin level. 24 They concluded that KTA may be safe in patients with HCV þ compensated cirrhosis. Their average follow-up was 32 months.…”
Section: Discussionmentioning
confidence: 99%
“…In their study the negative prognosticators included recipient age and albumin level. 24 They concluded that KTA may be safe in patients with HCV þ compensated cirrhosis. Their average follow-up was 32 months.…”
Section: Discussionmentioning
confidence: 99%
“…Good survival rates have been obtained in these patients, especially if they have minimal or well-controlled liver disease 35. In patients undergoing renal transplantation in the setting of established cirrhosis and a hepatic portal venous gradient (HPVG) below 10 mmHg, a combined liver-kidney transplantation may be unnecessary and a kidney transplant alone may be safely performed 36,37…”
Section: Hcv Infection In Kidney Transplant Recipientsmentioning
confidence: 99%
“…The authors concluded that kidney alone transplant may be safe in ESKD patients with compensated HCV cirrhosis and HPVG of less than 10 mmHg. (Paramesh et al, 2012). While limited studies suggest that combined liver-kidney transplant may be unnecessary in ESKD patients with compensated HCV cirrhosis and HPVG of less than 10 mmHg, patients with decompensated liver cirrhosis should be referred for combined liver-kidney transplant.…”
Section: Infectionsmentioning
confidence: 99%